Upper Primary Learners’ Level of Critical Thinking Skill and Its Effect on Students’ English Language Achievement in relation with Sex - Yohannes Sisay Molla (BIRCU, 2019)
The present study examined the nature of upper second cycle elementary school students’ critical thinking ability, investigated the correlation of critical thinking skill with learners’ English language achievement and sex, and explored the effect of critical thinking ability on learners' English language achievement. The study involved 99 grade seven students from two government full cycle primary schools in Woldia town. In order to gather data, standardized critical thinking test was administered and semester based learners’ English language achievement scores were used. So, T-test, Pearson product moment correlation and linear regression ware employed to analyze the data. Results of t-test applied to analyze the critical thinking test results revealed that participants’ level of critical thinking skill was very low, and the mean difference between female and male students’ critical thinking score was not statistically significant. However, the result of Pearson product moment correlation coefficient showed that there was a positive significant correlation between the critical thinking ability and English language achievement; whereas, correlation was not found between learners’ critical thinking proficiency and sex. The finding from the linear regression also exposed that learners’ critical thinking proficiency could predict approximately 36 % of learners’ English language achievement. Finally, the researchers made conclusions and forwarded recommendations based on the findings.